2017
DOI: 10.15171/jpid.2017.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antiplaque Efficacy of Commercially Available HiOra (Herbal) Mouthwash with Listerine Mouthwash: A Clinical Study

Abstract: Background. Herbal mouthwashes nowadays are gaining popularity because they contain naturally occurring ingredients that achieve the desired antimicrobial and antiinflammatory effects. The aim of this study was to compare the efficacy of a commercially available herbal mouthwash (HiOra) with that of an essential oil-containing mouthwash, Listerine. Methods. A single-blind cross-over study was conducted on 30 dental students aged 18‒25 years. The subjects were randomly divided into two groups: A and B (n=15) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The strong response of the two Listerine ® mouthwashes in this evaluation reflects the well-known and well-reported clinical performance of Listerine ® essential oil mouthwashes [24,[42][43][44][45][46], and demonstrates this model's sensitivity to essential oils. Even earlier than the evaluations of Dr. Miller [47], Listerine was among the first mouthwashes available to the public, though originally, the formula was not intended for oral care primarily but for other personal hygiene purposes [48].…”
Section: Discussionsupporting
confidence: 57%
“…The strong response of the two Listerine ® mouthwashes in this evaluation reflects the well-known and well-reported clinical performance of Listerine ® essential oil mouthwashes [24,[42][43][44][45][46], and demonstrates this model's sensitivity to essential oils. Even earlier than the evaluations of Dr. Miller [47], Listerine was among the first mouthwashes available to the public, though originally, the formula was not intended for oral care primarily but for other personal hygiene purposes [48].…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, its regular and extended use should be avoided [7]. Listerine is a mouthwash made in an attempt to reduce the side effects of CHX; it is effective in controlling halitosis and caries, but as it contains alcohol, there have been complaints about its unpleasant taste [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…From the results of the study, they concluded that both mouthwashes yielded comparable results in plaque reduction, thus highlighting the role of herbal mouthwash as a potent antiplaque agents. 14…”
Section: Efficacy Of Mouthwashes In Gingivitis Patientsmentioning
confidence: 99%